Evaluating Five Escherichia coli Derivative Strains as a Platform for Arginine Deiminase Overproduction - Abdollahi, Sara; Morowvat, Mohammad H.; Savardashtaki, Amir; Irajie, Cambyz; Najafipour, Sohrab; Ghasemi, Younes (Recent Patents on Biotechnology, 2022)
Aims: This study attempted to evaluate the five host strains, including BL21 (DE3), Rosetta (DE3), DH5α, XL1-BLUE, and SHuffle, in terms of arginine deiminase (ADI) production and enzyme activity. Background: Escherichia coli is one of the most preferred host microorganisms for the production of recombinant proteins due to its well-characterized genome, availability of various expression vectors, and host strains. Choosing a proper host strain for the overproduction of a desired recombinant protein is very important because of the diversity of genetically modified expression strains. Various E. coli cells have been examined in different patent applications. Methods: ADI was chosen as a bacterial enzyme that degrades L-arginine. It is effective in the treatment of some types of human cancers like melanoma and hepatocellular carcinoma (HCC), which are arginine-auxotrophic. Five mentioned E. coli strains were cultivated. The pET-3a was used as the expression vector. The competent E. coli cells were obtained through the CaCl2 method. It was then transformed with the construct of pET3a-ADI using the heat shock strategy. The ADI production levels were examined by 10% SDS-PAGE analysis. The ability of host strains for the expression of the requested recombinant protein was compared. The enzymatic activity of the obtained recombinant ADI from each studied strain was assessed by a colorimetric 96-well microtiter plate assay. Results: All the five strains exhibited a significant band at 46 kDa. BL21 (DE3) produced the highest amount of ADI protein, followed by Rosetta (DE3). The following activity assay showed that ADI from BL21 (DE3) and Rosetta (DE3) had the most activity. Conclusion: There are some genetic and metabolic differences among the various E. coli strains, leading to differences in the amount of recombinant protein production. The results of this study can be used for the efficacy evaluation of the five studied strains for the production of similar pharmaceutical enzymes. The strains also could be analyzed in terms of proteomics.
Keywords: Escherichia coli